Effects of marine diesel on microbial diversity and activity in high Arctic beach sediments - Margaux Durand; David Touchette; Ya-Jou Chen; Elisse Magnuson; Jessica Wasserscheid; Charles W. Greer; Lyle G. Whyte; Ianina Altshuler (Marine Pollution Bulletin, 2023)

Biodegradation potential of residue generated during the in-situ burning of oil in the marine environment - Ruby Pyke; Nathalie Fortin; Jessica Wasserscheid; Julien Tremblay; Lars Schreiber; Marie-Josee Levesque; Stephanie Messina-Pacheco; Lyle Whyte; Feiyue Wang; Kenneth Lee; David Cooper; Charles W. Greer (Journal of Hazardous Materials, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Thiomicrorhabdus streamers and sulfur cycling in perennial hypersaline cold springs in the Canadian high Arctic - Elisse Magnuson; Nadia C.S. Mykytczuk; Andre Pellerin; Jacqueline Goordial; Susan M. Twine; Boswell Wing; Simon J. Foote; Kelly Fulton; Lyle G. Whyte (Environmental Microbiology, 2021)
Summary The Gypsum Hill (GH) springs on Axel Heiberg Island in the Canadian high Arctic are host to chemolithoautotrophic, sulfur‐oxidizing streamers that flourish in the high Arctic winter in water temperatures from −1.3 to 7°C with ~8% salinity in a high Arctic winter environment with air temperatures commonly less than −40°C and an average annual air temperature of −15°C. Metagenome sequencing and binning of streamer samples produced a 96% complete Thiomicrorhabdus sp. metagenome‐assembled genome representing a possible new species or subspecies. This is the most cold‐ and salt‐extreme source environment for a Thiomicrorhabdus genome yet described. Metaproteomic and metatranscriptomic analysis attributed nearly all gene expression in the streamers to the Thiomicrorhabdus sp. and suggested that it is active in CO 2 fixation and oxidation of sulfide to elemental sulfur. In situ geochemical and isotopic analyses of the fractionation of multiple sulfur isotopes determined the biogeochemical transformation of sulfur from its source in Carboniferous evaporites to biotic processes occurring in the sediment and streamers. These complementary molecular tools provided a functional link between the geochemical substrates and the collective traits and activity that define the microbial community's interactions within a unique polar saline habitat where Thiomicrorhabdus ‐dominated streamers form and flourish.

Species interactions and distinct microbial communities in high Arctic permafrost affected cryosols are associated with the CH 4 and CO 2 gas fluxes - Ianina Altshuler; Jérémie Hamel; Shaun Turney; Elisse Magnuson; Roger Lévesque; Charles W. Greer; Lyle G. Whyte (Environmental Microbiology, 2019)
Summary Microbial metabolism of the thawing organic carbon stores in permafrost results in a positive feedback loop of greenhouse gas emissions. CO 2 and CH 4 fluxes and the associated microbial communities in Arctic cryosols are important in predicting future warming potential of the Arctic. We demonstrate that topography had an impact on CH 4 and CO 2 flux at a high Arctic ice‐wedge polygon terrain site, with higher CO 2 emissions and lower CH 4 uptake at troughs compared to polygon interior soils. The pmoA sequencing suggested that USCα cluster of uncultured methanotrophs is likely responsible for observed methane sink. Community profiling revealed distinct assemblages across the terrain at different depths. Deeper soils contained higher abundances of Verrucomicrobia and Gemmatimonadetes , whereas the polygon interior had higher Acidobacteria and lower Betaproteobacteria and Deltaproteobacteria abundances. Genome sequencing of isolates from the terrain revealed presence of carbon cycling genes including ones involved in serine and ribulose monophosphate pathways. A novel hybrid network analysis identified key members that had positive and negative impacts on other species. Operational Taxonomic Units (OTUs) with numerous positive interactions corresponded to Proteobacteria , Candidatus Rokubacteria and Actinobacteria phyla, while Verrucomicrobia and Acidobacteria members had negative impacts on other species. Results indicate that topography and microbial interactions impact community composition.

Macroinvertebrate and soil prokaryote communities in the forest–tundra ecotone of the Subarctic Yukon - Shaun Turney; Ianina Altshuler; Lyle G. Whyte; Christopher M. Buddle (Polar Biology, 2018)

Mechanisms of subzero growth in the cryophile Planococcus halocryophilus determined through proteomic analysis - Isabelle Raymond‐Bouchard; Karuna Chourey; Ianina Altshuler; Ramsunder Iyer; Robert L. Hettich; Lyle G. Whyte (Environmental Microbiology, 2017)
Summary The eurypsychrophilic bacterium Planococcus halocryophilus is capable of growth down to −15°C, making it ideal for studying adaptations to subzero growth. To increase our understanding of the mechanisms and pathways important for subzero growth, we performed proteomics on P . halocryophilus grown at 23°C, 23°C with 12% w/v NaCl and −10°C with 12% w/v NaCl. Many proteins with increased abundances at −10°C versus 23°C also increased at 23C‐salt versus 23°C, indicating a closely tied relationship between salt and cold stress adaptation. Processes which displayed the largest changes in protein abundance were peptidoglycan and fatty acid (FA) synthesis, translation processes, methylglyoxal metabolism, DNA repair and recombination, and protein and nucleotide turnover. We identified intriguing targets for further research at −10°C, including PlsX and KASII (FA metabolism), DD‐transpeptidase and MurB (peptidoglycan synthesis), glyoxalase family proteins (reactive electrophile response) and ribosome modifying enzymes (translation turnover). PemK/MazF may have a crucial role in translational reprogramming under cold conditions. At −10°C P . halocryophilus induces stress responses, uses resources efficiently, and carefully controls its growth and metabolism to maximize subzero survival. The present study identifies several mechanisms involved in subzero growth and enhances our understanding of cold adaptation.

Comparative activity and functional ecology of permafrost soils and lithic niches in a hyper‐arid polar desert - Jacqueline Goordial; Alfonso Davila; Charles W. Greer; Rebecca Cannam; Jocelyne DiRuggiero; Christopher P. McKay; Lyle G. Whyte (Environmental Microbiology, 2017)
Summary Permafrost in the high elevation McMurdo Dry Valleys of Antarctica ranks among the driest and coldest on Earth. Permafrost soils appear to be largely inhospitable to active microbial life, but sandstone lithic microhabitats contain a trophically simple but functional cryptoendolithic community. We used metagenomic sequencing and activity assays to examine the functional capacity of permafrost soils and cryptoendolithic communities in University Valley, one of the most extreme regions in the Dry Valleys. We found metagenomic evidence that cryptoendolithic microorganisms are adapted to the harsh environment and capable of metabolic activity at in situ temperatures, possessing a suite of stress response and nutrient cycling genes to fix carbon under the fluctuating conditions that the sandstone rock would experience during the summer months. We additionally identified genes involved in microbial competition and cooperation within the cryptoendolithic habitat. In contrast, permafrost soils have a lower richness of stress response genes, and instead the metagenome is enriched in genes involved with dormancy and sporulation. The permafrost soils also have a large presence of phage genes and genes involved in the recycling of cellular material. Our results underlie two different habitability conditions under extreme cold and dryness: the permafrost soil which is enriched in traits which emphasize survival and dormancy, rather than growth and activity; and the cryptoendolithic environment that selects for organisms capable of growth under extremely oligotrophic, arid and cold conditions. This study represents the first metagenomic interrogation of Antarctic permafrost and polar cryptoendolithic microbial communities.

Characterization of the microbial community structure and the physicochemical properties of produced water and seawater from the Hibernia oil production platform - C. William Yeung; Kenneth Lee; Susan Cobanli; Tom King; Jay Bugden; Lyle G. Whyte; Charles W. Greer (Environmental Science and Pollution Research, 2015)

Characterizing the surface-exposed proteome of Planococcus halocryophilus during cryophilic growth - Jennifer Ronholm; Isabelle Raymond-Bouchard; Marybeth Creskey; Terry Cyr; Edward A. Cloutis; Lyle G. Whyte (Extremophiles, 2015)

Evidence of in situ microbial activity and sulphidogenesis in perennially sub-0 °C and hypersaline sediments of a high Arctic permafrost spring - Guillaume Lamarche-Gagnon; Raven Comery; Charles W. Greer; Lyle G. Whyte (Extremophiles, 2015)

Microbial diversity and activity in hypersaline high Arctic spring channels - Chih-Ying Lay; Nadia C. S. Mykytczuk; Thomas D. Niederberger; Christine Martineau; Charles W. Greer; Lyle G. Whyte (Extremophiles, 2012)

Novel sulfur‐oxidizing streamers thriving in perennial cold saline springs of the Canadian high Arctic - Thomas D. Niederberger; Nancy N. Perreault; John R. Lawrence; Jay L. Nadeau; Randall E. Mielke; Charles W. Greer; Dale T. Andersen; Lyle G. Whyte (Environmental Microbiology, 2009)
Summary The perennial springs at Gypsum Hill (GH) and Colour Peak (CP), situated at nearly 80°N on Axel Heiberg Island in the Canadian high Arctic, are one of the few known examples of cold springs in thick permafrost on Earth. The springs emanate from deep saline aquifers and discharge cold anoxic brines rich in both sulfide and sulfate. Grey‐coloured microbial streamers form during the winter months in snow‐covered regions of the GH spring run‐off channels (−1.3°C to 6.9°C, ∼7.5% NaCl, 0–20 p.p.m. dissolved sulfide, 1 p.p.m. dissolved oxygen) but disappear during the Arctic summer. Culture‐ and molecular‐based analyses of the 16S rRNA gene (FISH, DGGE and clone libraries) indicated that the streamers were uniquely dominated by chemolithoautotrophic sulfur‐oxidizing Thiomicrospira species . The streamers oxidized both sulfide and thiosulfate and fixed CO 2 under in situ conditions and a Thiomicrospira strain isolated from the streamers also actively oxidized sulfide and thiosulfate and fixed CO 2 under cold, saline conditions. Overall, the snow‐covered spring channels appear to represent a unique polar saline microhabitat that protects and allows Thiomicrospira streamers to form and flourish via chemolithoautrophic, phototrophic‐independent metabolism in a high Arctic winter environment characterized by air temperatures commonly below −40°C and with an annual average air temperature of −15°C. These results broaden our knowledge of the physical and chemical boundaries that define life on Earth and have astrobiological implications for the possibility of life existing under similar Martian conditions.

Microbial diversity and activity through a permafrost/ground ice core profile from the Canadian high Arctic - Blaire Steven; Wayne H. Pollard; Charles W. Greer; Lyle G. Whyte (Environmental Microbiology, 2008)
Summary Culture‐dependent and culture‐independent methods were used in an investigation of the microbial diversity in a permafrost/massive ground ice core from the Canadian high Arctic. Denaturing gradient gel electrophoresis as well as Bacteria and Archaea 16S rRNA gene clone libraries showed differences in the composition of the microbial communities in the distinct core horizons. Microbial diversity was similar in the active layer (surface) soil, permafrost table and permafrost horizons while the ground ice microbial community showed low diversity. Bacteria and Archaea sequences related to the Actinobacteria (54%) and Crenarchaeota (100%) respectively were predominant in the active layer while the majority of sequences in the permafrost were related to the Proteobacteria (57%) and Euryarchaeota (76%) . The most abundant phyla in the ground ice clone libraries were the Firmicutes (59%) and Crenarchaeota (82%). Isolates from the permafrost were both less abundant and diverse than in the active layer soil, while no culturable cells were recovered from the ground ice. Mineralization of [1‐ 14 C] acetic acid and [2‐ 14 C] glucose was used to detect microbial activity in the different horizons in the core. Mineralization was detected at near ambient permafrost temperatures (−15°C), indicating that permafrost may harbour an active microbial population, while the low microbial diversity, abundance and activity in ground ice suggests a less hospitable microbial habitat.

Prokaryotic diversity of arctic ice shelf microbial mats - Eric M. Bottos; Warwick F. Vincent; Charles W. Greer; Lyle G. Whyte (Environmental Microbiology, 2008)
Summary The prokaryotic diversity and respiratory activity of microbial mat communities on the Markham Ice Shelf and Ward Hunt Ice Shelf in the Canadian high Arctic were analysed. All heterotrophic isolates and > 95% of bacterial 16S rRNA gene clone library sequences from both ice shelves grouped within the phyla Bacteroidetes , Proteobacteria and Actinobacteria . Clone library analyses showed that the bacterial communities were diverse and varied significantly between the two ice shelves, with the Markham library having a higher estimated diversity (Chao1 = 243; 105 operational taxonomic units observed in 189 clones) than the Ward Hunt library (Chao1 = 106; 52 operational taxonomic units observed in 128 clones). Archaeal 16S rRNA gene clone libraries from both ice shelves were dominated by a single Euryarchaeota sequence, which appears to represent a novel phylotype. Analyses of community activity by radiorespiration assays detected metabolism in mat samples from both ice shelves at temperatures as low as −10°C. These findings provide the first insight into the prokaryotic biodiversity of Arctic ice shelf communities and underscore the importance of these cryo‐ecosystems as a rich source of microbiota that are adapted to extreme cold.

Microbial ecology and biodiversity in permafrost - Blaire Steven; Richard Léveillé; Wayne H. Pollard; Lyle G. Whyte (Extremophiles, 2006)

Alkane hydroxylase homologues in Gram‐positive strains - Jan B. Van Beilen; Theo H. M. Smits; Lyle G. Whyte; Susanne Schorcht; Martina Röthlisberger; Thorsten Plaggemeier; Karl‐Heinrich Engesser; Bernard Witholt (Environmental Microbiology, 2002)
Summary We isolated Gram‐positive alkane‐degraders from soil and a tricking‐bed reactor, and show using polymerase chain reaction (PCR) with degenerate alkane hydroxylase primers and Southern blots that most Rhodococcus isolates contain three to five quite divergent homologues of the Pseudomonas putida GPo1 alkB gene. Two Mycobacterium isolates each contain one homologue, however there is no evidence for the presence of alkB homologues in the remaining strains.